Desain Pembelajaran Materi Himpunan Dengan Pendekatan Realistic Mathematics Education (RME) Untuk Kelas VII - Manurung, Mika Meitriana; Windria, Hening; Arifin, Samsul (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
The topic of the set is a basic concept in mathematics and its relationship is close to our daily life. However, some studies in Indonesia have found that the students have difficulties in solving the set problem. This can be due to the pattern of mathematics teaching in schools. This study aims to provide a design of learning in the set topic with Realistic Mathematics Education (RME) approach. The research questions are: (1) How is the design of mathematics learning in the topic of the set using the RME approach? (2) How do students learn the topic of the set by using the RME approach? This research method is design research with one cycle in SMP Dasana Indah Tangerang. The subjects were 24 students with one focus group, 5 students who had no errors in the initial test. Data of research obtained from sound recording, video, photos, and Student Activity Sheet, then be analyzed by comparing the Hypothesis of Trajectory Learning and Trajectory of Actual Learning. This study produces the Theory of Local Instruction, with four lessons, namely: (1) Determining the set and not the set; (2) Finding the concept of set of universe, subsets, empty set, and describing the models; (3) Finding the concept of intersection, union, and illustrating the models; (4) Find the concept of complement, difference, and describe the models, and use the models to solve the story problem. In the learning process, through grouping games and describe the model, student learning the notion of set enthusiastically and actively.Â Keywords: design research, set, realistic mathematics education approach